Mixed Signals - Anastasia Papushina (Journal of Festive Studies)
The October Revolution of 1917 introduced a new array of revolutionary festivals, prompting a series of debates concerning the appropriate manner of their celebration and the significance they should hold within the unique context of Soviet Russia. Festival organizers endeavored to reimagine several foundational aspects of commemorating special dates. This article examines the paradoxes and inconsistencies between the intended meanings of early Soviet festivals and their actual manifestations. The author highlights the conflicting messages that characterized this aspect of early Soviet culture, revealing the underlying tensions in the attempt to establish a cohesive revolutionary identity through these celebrations.